Exploring the gut microbiome’s role in colorectal cancer: diagnostic and prognostic implications - Chen, Guoming; Ren, Qing; Zhong, Zilan; Li, Qianfan; Huang, Zhiqiang; Zhang, Cheng; Yuan, Hongchao; Feng, Zixin; Chen, Bonan; Wang, Ning; Feng, Yibin (Frontiers in Immunology, 2024)
The intricate interplay between the gut microbiome and colorectal cancer (CRC) presents novel avenues for early diagnosis and prognosis, crucial for improving patient outcomes. This comprehensive review synthesizes current findings on the gut microbiome's contribution to CRC pathogenesis, highlighting its potential as a biomarker for non-invasive CRC screening strategies. We explore the mechanisms through which the microbiome influences CRC, including its roles in inflammation, metabolism, and immune response modulation. Furthermore, we assess the viability of microbial signatures as predictive tools for CRC prognosis, offering insights into personalized treatment approaches. Our analysis underscores the necessity for advanced metagenomic studies to elucidate the complex microbiome-CRC nexus, aiming to refine diagnostic accuracy and prognostic assessment in clinical settings. This review propels forward the understanding of the microbiome's diagnostic and prognostic capabilities, paving the way for microbiome-based interventions in CRC management.